Norse Mythology - Gaiman, Neil (London Bloomsbury, 2017)
"In Norse Mythology, Gaiman fashions primeval stories into a novelistic arc that begins with the genesis of the legendary nine worlds; delves into the exploits of the deities, dwarves, and giants; and culminates in Ragnarok, the twilight of the gods and the rebirth of a new time and people. Gaiman stays true to the myths while vividly reincarnating Odin, the highest of the high, wise, daring, and cunning; Thor, Odin's son, incredibly strong yet not the wisest of gods; and Loki, the son of a giant, a trickster and unsurpassable manipulator."--Container.
Include Glossary and Note
Keywords: Mythology, Norse